KHAT USE PREVALENCE, CAUSES AND ITS EFFECT ON MENTAL HEALTH, BAHIR-DAR, NORTH WEST ETHIOPIA - Gebiresilus, Asfaw Getnet; Gebresilus, Berhanie Getnet; Yizengaw, Simegn Sendek; Sewasew, Daniel Tsehay; Mengesha, Teka Zewudie (European Scientific Journal, ESJ, 2014)
The main objectives of this study were to assess the prevalence, causes and effects of khat chewing on levels of anxiety, depression and social-skills of Bahir-Dar University (BDU) students who have an experience of khat chewing. Methods: For this study, 154 (i.e. 112 khat users and 42 non-khat users) participants were selected using repeated survey sampling. The levels of anxiety and depression were assessed using anxiety and depression symptoms inventory and the level of social-skill was assessed using social avoidance and distress scale. The analysis was made using descriptive statistics like frequency, minimum, maximum, mean, correlation; and inferential statistics like one-way ANOVA. Along with, thematic analysis for qualitative data was used. The study revealed that 33% and 67% of khat users were categorized as dependent khat users and non-dependent khat users respectively. Some of the worsening factors of khat chewing were; the high production khat in the area and khat chewing houses in the nearby university villages, and nonattendance of awareness creating opportunities on the psychological, social and economic influence as a result of khat use. The expense was highly affecting the life of students mainly when they were frequent chewers of khat. Statistically significant difference was found in the levels of anxiety (p<0.01) and depression (p<0.05) between dependent khat users, nondependent khat users and non-khat users. However, statistically significant variation was not obtained on the level of social-skills among the three groups (p>0.05). Anxiety and depression are determined by the level of dependence, dependent khat users higher level of experience as compared to nondependent khat users and non-khat users. Therefore, it is not becoming a khat user, but developing dependency on khat which is associated with anxiety and depression. Many factors worsening khat chewing and the usage of khat was uneconomical for university students.